Explicating the resource integration process during self-service socialisation: Conceptual framework and research propositions - van Tonder, Estelle; Saunders, Stephen Graham; Farquhar, Jillian Dawes (Journal of business research, 2020)
Little is known about self-service socialisation and the resource integration process that may transpire when customers help other less-skilled customers with self-services. Insight into these matters is important as the process may affect other customers’ skill development and ability to contribute meaningfully to value co-creation in the service ecosystem. Accordingly, this research develops a conceptual framework and four research propositions outlining customers’ resource integration approaches towards other customers during socialisation and service exchange, as informed by their institutions endorsing either self-reliant or compliant practices. Insight is also provided into the extent to which the resource integration approaches (transpiring against the background of customers’ engagement with firms’ self-service resources) may enable other customers to participate in meaningful service exchanges in the service ecosystem. Effectively, the framework advances business understandings of the distinct roles that customers may perform when socialising other customers about self-services.